THEOLOGICAL ANALYSIS OF THE INTERPRETATION OF SEVENTH DAY ADVENTIST KIWI CHURCH CONGREGATION OF SONGS BY DOING ENERGIZER IN PRAISING GOD ACCORDING TO PSALM 149:3 - Gloria Chika; Bartolomeus D. Nainggolan (Fakultas Filsafat Universitas Advent Indonesia, 2018)
In this research, the author tries to analyse the the causes of congregational membersperforming energizer at the church in praising God based on the Psalm 149:3 in theSDA Kiwi church. Therefore the purpose of this study is to know the extent of theirunderstanding of the background context of Psalm 149:3. The use energizers inpraising God in church worship and the right place to perform the songs andenergizer referred to in Psalm 149:3. This research is divided into two parts, namelythe theory and field research through literatuure study is to understanding how topraise God using energizer. While the results and field research questionnaire is toobtain the extent of their understanding of the four indicators: (1) Dance andenergizer in praising God; (2) What is the meaning of the dance in Psalm 149:3; (3)Can we use of hands or dance in praising God in worship; (4) Where is the rightplace to perform dance and song according to Psalm 149:3. Finally, throughanswers from 30 respondents, it was found that they understood well both the pointsof the four indicators. However, there are also some unfamiliar understanding of theitems of the four indicators. Thus the results of this study are in particularlyexpected to support and strengthen the understanding Kiwi Seventh-day AdventistsChurch. In general, this research is also expected to be useful for all christian inIndonesia.